Isotope hydrology and baseflow geochemistry in natural and human-altered watersheds in the Inland Pacific Northwest, USA - Sanchez-Murillo, Ricardo (2015)
This study presents a stable isotope hydrology and geochemical analysis in the inland Pacific Northwest (PNW) of the USA. Isotope ratios were used to estimate mean transit times (MTTs) in natural and human-altered watersheds using the FLOWPC program. Isotope ratios in precipitation resulted in a regional meteoric water line of δ2H = 7.42·δ18O + 0.88 (n = 316; r2 = 0.97). Isotope compositions exhibited a strong temperature-dependent seasonality. Despite this seasonal variation, the stream δ18O variation was small. A significant regression (τ = 0.11D−1.09; r2 = 0.83) between baseflow MTTs and the damping ratio was found. Baseflow MTTs ranged from 0.4 to 0.6 years (human-altered), 0.7 to 1.7 years (mining-altered), and 0.7 to 3.2 years (forested). Greater MTTs were represented by more homogenous aqueous chemistry whereas smaller MTTs resulted in more dynamic compositions. The isotope and geochemical data presented provide a baseline for future hydrological modelling in the inland PNW.